The Role of Social Class vs. Income in The Purchase of Consumer Products in Jawa Timur - Anna Triwijayati; Melany Melany; Dian Wijayanti; Deviga Bayu Pradipta (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Social class and income are related to purchasing behavior. This research utilized a quantitative survey with an ex-post-facto approach, which is aimed to find out the relationship and difference between social class and income with the purchase of consumer goods and services in Jawa Timur. Respondents were classified by social classes and income levels using the Index of Social Position (ISP); the respondents then filled out a questionnaire on 18 items of purchase grouped into five types, which are food and beverages, clothing, durable goods, investment services, and other products. The data analysis was conducted with the chi-square technique. Analysis results showed that social class is linked with the purchase of 17 items, while income level correlates with all items of products and services that are used. Social class is more linked to milk, fast food, owned and the price of personal and household electronic equipment, and the type of investments and finances. Meanwhile, income is more related to meat, soft drink, clothing, type and price of the utilized vehicle.